Strategi Guru dalam Pemanfaatan Media Bahan Alam dan Lingkungan Sekitar untuk Meningkatkan Kreativitas Anak Usia Dini di PAUD Melati Duko Rubaru Sumenep - Ulfah, Ulfah (Indo-MathEdu Intellectuals Journal, 2024)
This research discusses the development of creativity in early childhood through the use of natural materials and the surrounding environment in pre-school education. A supportive environment, including the role of professional teachers, is considered crucial for facilitating children's creativity. Although natural materials offer creative opportunities, challenges such as material durability and management by teachers still need to be overcome. This research focuses on teachers' strategies for utilizing natural materials and the surrounding environment and exploring their advantages and disadvantages. The method in this research uses a qualitative descriptive approach, this research was conducted at PAUD Melati Duko Rubaru Sumenep using interviews and observation as data collection techniques. Data analysis was carried out using qualitative descriptive analysis techniques on the results of interviews and observations. The research results show that the use of natural media and the surrounding environment has made a positive contribution in stimulating children's creativity, although challenges remain. Some effective teacher strategies include using banana stems and leaves for artistic activities as well as cardboard media for children's independent creations. In conclusion, this approach provides important insights into the importance of using natural media in pre-school education and provides recommendations for further development in the context of early childhood education